Fine‐Tuning of Superhydrophobicity Based on Monolayers of Well‐defined Raspberry Nanoparticles with Variable Dual‐roughness Size and Ratio. (14th July 2014) - Carcouët, Camille C. M. C.; Esteves, A. Catarina C.; Hendrix, Marco M. R. M.; van Benthem, Rolf A. T. M.; de With, Gijsbertus
<x xml:space="preserve">Abstract</x> Superhydrophobic surfaces have been extensively investigated for self‐cleaning, low‐adhesion, anti‐corrosion or reduced‐drag applications. Roughness and its characteristics, i.e., morphology, overall roughness and individual feature size, is an essential factor for superhydrophobicity. Several experimental methods and theoretical models strived to predict how the surface wettability is affected by the surface roughness. However, due to the difficulty of making practical surfaces with well‐defined roughness profiles, only limited and arbitrary experimental studies focused on practical superhydrophobic films. Here, the roughness factors which determine the wetting properties of films are reported, based on monolayers of well‐defined raspberry silica‐silica nanoparticles, exhibiting a wide‐range and systematic variation of individual features sizes and ratios (large over small features). The advancing water contact angle does not depend on the feature size or ratio, while the contact angle hysteresis (CAH) is strongly dependent on both. The minimum size and size ratio to reach superhydrophobicity were determined. These new insights into the wetting of rough surfaces can be used to direct the design of practical superhydrophobic materials for advanced applications such as solar panels, microelectronics or microfluidic devices.